Conceptualizing a credits trading approach towards corporate social responsibility credits - Hede, Shantesh (2013)
Life Cycles of both products and services significantly consume renewable and non-renewable resources across a worldwide scale. Thus, eliciting an enormous environmental impact, that is known to disproportionately instigate crises into the socio-economic and political domains of our civilization. Therefore, Creation of Shared Value and Corporate Social Responsibility (CSR) have been considered by Policy makers, Public and Private Institutions. In addition to Corporate Philanthropy, CSR practices also encompass a wide spectrum of activities, including Stakeholder safety/welfare, designing sustainable products and ecological restoration to name a few which are ascertained to capital and knowledge intensive in nature. Therefore, this paper primarily structures the scope of CSR and proposes a mechanism for trading Corporate Social Responsibility credits in order to incentivize stakeholder centered business practices. Furthermore, the CSR credits trading methodology would entail similar mechanisms used by its remotely successful predecessors namely, tax incentives, tradable credits/certificates and flexible mechanisms for implementing sustainable projects. The CSR credits trading methodology is envisioned to entail a more holistic approach towards overall Sustainability when compared to Carbon Offsets/Renewable Energy Certificates which are more focused towards reducing the environmental footprint.